Reproductive development of common buckwheat (Fagopyrum esculentum Moench) and its wild relatives provides insights into their evolutionary biology - Sokoloff, Dmitry D.; Malyshkina, Raisa A.; Remizowa, Margarita V.; Rudall, Paula J.; Fomichev, Constantin I.; Fesenko, Aleksey N.; Fesenko, Ivan N.; Logacheva, Maria D. (Frontiers in Plant Science, 2023)
The developmental morphology of Common buckwheat (Fagopyrum esculentum) is insufficiently investigated to understand its inflorescence architecture, which is crucial for crop yield. To address this problem, we explored patterns of flower structure and arrangement in buckwheat and its wild relatives, using comparative morphology, scanning electron microscopy and X-ray microtomography. In Fagopyrum and many other Polygonaceae, an important inflorescence module is a thyrse. The primary axis of a thyrse never terminates in a flower and lateral cymes (monochasia) produce successively developing flowers of several orders. Each flower of a cyme is enclosed together with the next-order flower by a bilobed sheathing bract-like structure of controversial morphological nature. Our data support interpretation of the bract as two congenitally fused phyllomes (prophylls), one of which subtends a next-order flower. In a homeotic mutant of F. esculentum, tepal-like bract, the bilobed sheathing bract-like organ acquires tepal-like features and is sometimes replaced by two distinct phyllomes. Wild representatives of F. esculentum (ssp. ancestrale) and most cultivars of the Common buckwheat possess an indeterminate growth type with lateral thyrses produced successively on the primary inflorescence axis until cessation of growth. In contrast, determinate cultivars of F. esculentum develop a terminal thyrse after producing lateral thyrses. Several species of Fagopyrum show infraspecific variation in overall inflorescence morphology. In F. tataricum, a terminal thyrse does not guarantee a more synchronized flowering pattern, with implications for crop yield. The genus Fagopyrum offers an excellent opportunity for evo-devo studies related to inflorescence architecture.